Upaya Preventif Kehamilan Remaja dengan Pendidikan Kesehatan Mengenai Kesehatan Reproduksi pada Remaja di Kecamatan Indramayu - Mira Aryanti; Purwandyarti Apriliani; Intan Anggita (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
One of the efforts to prevent teenage pregnancy incidence is health education about teenage pregnancy in Adolescence; it is hoped that health education can help government programs reduce the incidence of teenage pregnancy in the Indramayu Regency. The TEAM carries out community service activities from the STIKes Indramayu Midwifery Study Program, which was implemented in early July-August 2019, located in the Margadadi and Plumbon Puskesmas area (two Puksemas located in the Indramayu District Work Area). Community service aims to improve the thinking skills and understanding of junior high school students in preventing teenage pregnancy in health education. The implementation method by using leaflets/brochures and preparing reproductive health education materials. It can be seen that before the extension, there were 102 students (60%) with low knowledge results, 58 students (34.1%) with sufficient knowledge, and ten students (5.9%) with good knowledge results. In contrast, the knowledge obtained from counseling and discussion showed a significant increase in knowledge about adolescent reproductive health; the results were 147 students (86.5%) with good knowledge of 23 students (13.5%) with sufficient knowledge. There is a change or increase in students' knowledge about adolescent reproductive health, especially about teenage pregnancy prevention. It is hoped that this community service education can reduce maternal and infant mortality rates caused by adolescent pregnancy.